2003
DOI: 10.1029/2002gb001995
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning net ecosystem carbon exchange into net assimilation and respiration using 13CO2 measurements: A cost‐effective sampling strategy

Abstract: The current emphasis on global climate studies has led the scientific community to set up a number of sites for measuring the long‐term biosphere‐atmosphere net CO2 exchange (net ecosystem exchange, NEE). Partitioning this flux into its elementary components, net assimilation (FA), and respiration (FR), remains necessary in order to get a better understanding of biosphere functioning and design better surface exchange models. Noting that FR and FA have different isotopic signatures, we evaluate the potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
187
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(198 citation statements)
references
References 38 publications
9
187
2
Order By: Relevance
“…A highly variable range in soil δ 13 C R of 0.3-12.5 ‰ occurred in an experimental garden with deciduous trees (Moyes et al, 2010). The information on dynamics of ecosystem respiration (δ 13 C R assessed by Keeling-plot approaches) presents again a very heterogeneous picture: while Ogée et al (2003) and Schnyder et al (2004) found only minor nocturnal variation of δ 13 C R (<3 ‰), others report that nocturnal ecosystem δ 13 C R presented the largest variation among different respiratory components (Kodama et al, 2008;Unger et al, 2010a). Nocturnal variations in δ 13 C R were 6.4 ‰ in a grassland (Bowling et al, 2003), 4.2-8.1 ‰ in a Mediterranean woodland (Werner et al, 2006;Unger et al, 2010a), 6.1 ‰ in a Pinus sylvestris stand (Kodama et al, 2008), 2.6-3.6 ‰ in a subalpine forest (Bowling et al, 2005;Riveros-Iregui et al, 2011), and 3.8 ‰ a beech-dominated deciduous forest (24 h-cycle, Knohl et al, 2005).…”
Section: New Methodological Developments In High Time-resolved Measurmentioning
confidence: 99%
“…A highly variable range in soil δ 13 C R of 0.3-12.5 ‰ occurred in an experimental garden with deciduous trees (Moyes et al, 2010). The information on dynamics of ecosystem respiration (δ 13 C R assessed by Keeling-plot approaches) presents again a very heterogeneous picture: while Ogée et al (2003) and Schnyder et al (2004) found only minor nocturnal variation of δ 13 C R (<3 ‰), others report that nocturnal ecosystem δ 13 C R presented the largest variation among different respiratory components (Kodama et al, 2008;Unger et al, 2010a). Nocturnal variations in δ 13 C R were 6.4 ‰ in a grassland (Bowling et al, 2003), 4.2-8.1 ‰ in a Mediterranean woodland (Werner et al, 2006;Unger et al, 2010a), 6.1 ‰ in a Pinus sylvestris stand (Kodama et al, 2008), 2.6-3.6 ‰ in a subalpine forest (Bowling et al, 2005;Riveros-Iregui et al, 2011), and 3.8 ‰ a beech-dominated deciduous forest (24 h-cycle, Knohl et al, 2005).…”
Section: New Methodological Developments In High Time-resolved Measurmentioning
confidence: 99%
“…In one study in particular, ignoring such gradients resulted in sensible heat 30 fluxes that were 61% of reference measured values (Baldocchi and Wilson, 2001). Other studies (Ogée et al, 2003;Carrer et al, 2013) also found that simulations of the energy budget were improved with the simulation of vertical profiles.…”
mentioning
confidence: 87%
“…The relatively short measurement time and field-capable operation of TDLAS instruments provides greater temporal and spatial resolution of [CO 2 ] and δ 13 C of CO 2 than flask-based techniques (Ogee et al, 2003;Mortazavi et al, 2005Mortazavi et al, , 2006. Observation of seasonal variation in the mole fraction and isotopic composition of atmospheric CO 2 is an obvious application that would benefit from increased temporal resolution (Lai et al, 2005(Lai et al, , 2006 cycles for [CO 2 ] and δ 13 C that are similar to those collected from the alpine tundra site (NWR) (smoothed line in Fig.…”
Section: Seasonal Differences In δ 13 C Versus [Co 2 ]mentioning
confidence: 99%
“…Conversely, at leaf to ecosystem scales the δ 13 C of CO 2 is mostly affected by photosynthesis (Farquhar et al, 1989) and by respiration from all autotrophic and heterotrophic organisms . Studies at these scales using flask-based sampling approaches may have temporal resolution on the order of hours (Knohl, 2003;Ogee et al, 2003), but lack seasonal or inter-annual resolution, and those that do address these timescales lack diurnal resolution (Lai et al, 2005;Alstad et al, 2007). TDLAS has the potential to greatly increase the number of measurements made at a single location and bridge the gap between diurnal and inter-annual timescales.…”
Section: Introductionmentioning
confidence: 99%